Pengaruh Akses Permodalan, Strategi Pemasaran dan Inovasi Produk terhadap Kinerja Usaha Konveksi di Kota Banda Aceh - Syadza Khaula Marzana; Khairul Amri; Dara Amanatillah (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This research aims to analyze the influence of access to capital, marketing strategy and product innovation on the performance of convection businesses in the city of Banda Aceh. The research sample was 59 business actors who run their businesses in Kampung Baru village as a convection business center in the city of Banda Aceh. Data was collected using a questionnaire and then the data was analyzed using multiple linear regression statistical equipment. This research reveals that access to capital, marketing strategies and product innovation can significantly improve the performance of convection businesses. The easier it is for business actors to access external capital sources, the better the marketing strategy implemented, the better the business performance. Likewise with product innovation, innovative business actors have better business performance than those who are less innovative. Therefore, increasing access to sources of capital, improving the ability of business actors to implement marketing strategies and innovating the products/services offered can be a recommended policy for relevant agencies in the city of Banda Aceh.